Edutainment of Using Tiktok in Learning English Vocabulary a Case Study of Secondary Student - Zein, Mutiara; Weny, Krisna; Br. Perangin-angin, Alemina (Universitas Methodist Indonesia, 2024)
This study aims to examine the use of TikTok as a tool of edutainment for English language acquisition among secondary school students. The research focuses on how TikTok enhances vocabulary development and improves students’ fluency in English. Using a qualitative survey method, data were gathered from 20 secondary school students through an online questionnaire. The result shows that students perceive TikTok as an effective medium for learning English, particularly in terms of expanding their vocabulary and improving their confidence in using the language. The findings suggest that TikTok’s visual and interactive content can motivate students to engage more actively in language learning. This study concludes that TikTok, when used thoughtfully, can be a valuable resource for language education, providing recommendations for educators and content creators to develop more engaging and educational material on the platform.